The Effect of Workload and Burnout on Job Stress among Regional Police Officers of South Sumatra through Resilience as an Intervening Variable - Diajeng Woro Ambiko; Zunaidah; Afriyadi Cahyadi (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
This study aims to examine the influence of workload and burnout on job stress among officers of the South Sumatra Regional Police (Polda Sumsel), with resilience serving as a mediating variable. A quantitative method with an explanatory research approach was employed, involving a survey of 294 personnel from the Special Criminal Investigation Directorate (Ditreskrimsus), General Criminal Investigation Directorate (Ditreskrimum), Traffic Directorate (Ditlantas), and Water and Air Police Directorate (Ditpolairud) of Polda Sumsel. Data were collected using a Likert-scale questionnaire and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results reveal that workload has a significant direct effect on job stress among police officers. Burnout also demonstrates a significant direct effect on job stress. Furthermore, both workload and burnout exert significant direct effects on resilience. Resilience has a significant direct effect on job stress. In addition, resilience significantly mediates the relationships between workload and job stress, as well as between burnout and job stress among police officers.